BOOK REVIEW: TEORI-TEORI DAN METODE PENGKAJIAN AMERIKA - Inayati, Rif'ah; Sriastuti, Anna (Rubikon : Journal of Transnational American Studies, 2025)
Quests in American Studies, along with discussions about the theories, methods, and practices that shape it, have been growing for decades as the study of American culture and society has undergone various changes in line with shifts in various scientific disciplines and changes within American Studies itself.  Henry Nash Smith’s article (1957, 197-208) entitled “Can American Studies Develop a Method?” explains that American Studies, in his understanding, is “the study of American culture, past and present, as a whole”; and by “culture” or “the way in which subjective experience is organized.” As Smith’s statement can be broad, Ida Rochani Adi offers readers of theories and methods in American Studies with broad, multi-faceted knowledge of America as a complex, diverse and dynamic nation, and its relationship with the broader world, within the myth-and-symbol school and transnational/post-national American Studies in her book entitled “Teori-Teori dan Metode Pengkajian Amerika”. Adi’s systematic, coherent, comprehensive, and applicable presentation makes this book a required reading for exploring and understanding American Studies, particularly in relation to theories and methods in interdisciplinary studies.